A preparation method and processing device of porous graphene film
By performing laser treatment and high-pressure pyrolysis treatment on flexible carbon-based film materials, the problem of difficult control of the specific surface area of porous graphene films in the prior art is solved, and an efficient and controllable preparation process is achieved, which improves the performance of the material and Application potential.
Patent Information
- Application Number
- CN202410690198.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing preparation methods of porous graphene film materials are difficult to accurately control the specific surface area of the porous graphene structure, and the preparation process is complex, high cost and low yield, which limits its large-scale application.
Using a flexible carbon-based film material as the carbon precursor material, hydrophilic modification is performed by the first laser beam, the activator solution is coated and crystallized, and then cross-overlap scanning and inducing activation is performed using the second and third laser beams. , combined with high-temperature pyrolysis treatment of high-voltage belt voltage rollers, a porous graphene film is gradually formed.
Accurate control of the specific surface area of porous graphene films, improve the controllability and efficiency of the preparation process, reduce costs, enhance the flexibility and foldability of the material, and the specific surface area of the prepared porous graphene film can reach 1,400. ~2000m2/g.
Smart Images

Figure CN118666275B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of graphene film processing, and in particular to a method for preparing a porous graphene film and a processing device thereof. Background Art
[0002] The application prospects of porous graphene film technology are broad. Due to its high specific surface area and adjustable pore structure, it can be used in energy storage devices, separation membranes, sensors, catalyst supports and biomedical fields. Porous graphene film not only maintains the high conductivity, high strength, strong chemical stability and other characteristics of graphene, making it an ideal candidate material for the preparation of functional films; it also has the characteristics of high specific surface area and excellent flexibility. It is also considered to be one of the most promising flexible energy storage materials and has attracted widespread attention in the field of wearable electronic devices and flexible micro energy storage devices.
[0003] The methods for preparing porous graphene film materials usually include: chemical vapor deposition, chemical solution method, carbon compound template method, etc. There are some shortcomings in the porous graphene films prepared by such traditional methods, such as complex preparation process: including the synthesis of precursor substances, adjustment of reaction conditions and subsequent treatment, etc.; high preparation cost and low yield: the required raw materials and equipment costs are high, which limits the large-scale application of porous graphene films. Due to the multiple steps and complex conditions in the preparation process, it is often difficult to accurately control the specific surface area of the porous graphene structure. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a porous graphene film to solve the problem that it is difficult to accurately control the specific surface area of the porous graphene structure in the existing method for preparing porous graphene film materials; the purpose of the present invention is to provide a processing device for a porous graphene film to realize the above-mentioned method for preparing the porous graphene film.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a porous graphene film, comprising the following steps:
[0007] S1: Select a flexible carbon-based film material, perform a hydrophilic modification treatment on the surface of the flexible carbon-based film material by a first laser beam, then uniformly coat an activator solution on the surface of the flexible carbon-based film material, and allow the activator solution to crystallize on the surface of the flexible carbon-based film material to obtain a carbon-based film material loaded with activator crystals;
[0008] S2: Cross-overlap scanning of the carbon-based film material loaded with activator crystals by a second laser beam to obtain a composite film, wherein the upper layer of the composite film is a uniform mixture of the carbon material and the activator, and the lower layer of the composite film is a flexible carbon-based film material;
[0009] S3: Inducing and activating the composite film with a third laser beam to obtain an activated graphene film material;
[0010] S4: using a high voltage roller to perform high temperature pyrolysis treatment on the activated graphene film material;
[0011] S5: Cleaning and drying the activated graphene membrane material in step S4 to obtain a porous graphene film.
[0012] In the method for preparing the porous graphene film, in step S1, the hydrophilic modification step includes: scanning a first laser beam on the smooth surface of the carbon-based film material, and processing a microstructure array pattern with a spacing of 40 to 100 μm and a depth of 10 to 15 μm, wherein the area of the microstructure array pattern is a surface modification area, and the area of the unprocessed microstructure array pattern is a non-surface modification area.
[0013] In the preparation method of the porous graphene film, in step S1, the coating step of the activator solution includes: first immersing the flexible carbon-based film material after hydrophilic modification into the activator solution to form a liquid film on the surface modified area; then taking out the flexible carbon-based film material after hydrophilic modification, and continuing to add the activator solution to the surface modified area, so that the activator solution evenly and completely covers the surface modified area; the thickness of the activator solution after crystallization is ≤15μm.
[0014] In the method for preparing the porous graphene film, in step S1, the flexible carbon-based film material includes one of polyimide film, polyimide paper, lignin biomass film, chitosan biomass film, phenolic resin and polybenzoxazine resin; the thickness of the flexible carbon-based film material is 50 to 200 μm.
[0015] In the method for preparing the porous graphene film, in step S1, the activator solution is crystallized on the surface of the flexible carbon-based film material by heating and drying, the drying temperature is 60-100° C., and the drying time is 5-15 min.
[0016] In the method for preparing the porous graphene film, in step S2, the second laser beam is emitted by an ultraviolet laser or a mid-infrared carbon dioxide laser;
[0017] The second laser beam performs cross-overlap scanning in a parallel scanning mode, the laser scanning direction is perpendicular to the transmission direction of the carbon-based thin film material loaded with activator crystals, the number of cross-overlap scanning is 5 to 10 times, and the scanning speed is 200 to 300 mm / s;
[0018] When using a UV picosecond laser for cross-overlap scanning, the laser power is 8.5 to 9.5 W and the laser scanning interval is 12.7 to 17.5 μm;
[0019] The ratio of the thickness of the uniform mixture of the upper carbon material and the activator of the composite film to the thickness of the lower flexible substrate is not less than 1:2.
[0020] When a mid-infrared carbon dioxide continuous laser is used for cross-overlap scanning, the laser power is 8 to 10 W and the laser scanning interval is 20 to 30 μm.
[0021] In the preparation method of the porous graphene film, in the step S3, the third laser beam is emitted by an ultraviolet picosecond laser, the scanning mode is a parallel scanning mode, the laser scanning direction is perpendicular to the transmission direction of the composite film, the laser power is 6.5-7.5W, and the scanning speed is 40-80mm / s; and the composite film is placed in an inert gas atmosphere for the third laser beam scanning; the wavelength of the ultraviolet picosecond laser is ≤355nm, and the laser pulse width is ≤12ps.
[0022] In the method for preparing the porous graphene film, in step S4, the voltage of the high-voltage voltage roller is 50-150V, the logarithm is 2-6, the temperature of the high-temperature pyrolysis treatment is 200-600°C, and the duration of the high-temperature pyrolysis treatment is 15-30 minutes.
[0023] In the preparation method of the porous graphene film, in step S5, the cleaning and drying steps include: soaking the activated graphene membrane material treated with high-temperature pyrolysis in a neutralizing solution and hot deionized water in sequence, wherein the temperature of the hot deionized water is 60-70°C, and the soaking time in the neutralizing solution and the soaking time in the deionized water are both 5-20 minutes; then washing in deionized water at room temperature until the pH value of the washed deionized water is neutral, and drying.
[0024] The present invention provides a processing device for a porous graphene film, which is used to implement the above-mentioned method for preparing the porous graphene film, and comprises an unwinding device, a laser pre-processing device, a laser carbonization device, a laser graphitization device, a Joule heating device, a post-processing device and a winding device which are arranged in sequence; the unwinding device is used to unwind the flexible carbon-based film, and the winding device is used to wind the porous graphene film;
[0025] The laser pre-treatment device comprises a first laser component, an activator solution pool, a drop coating component and a first drying component which are arranged in sequence; the first laser component is used to emit a first laser beam and perform surface hydrophilic treatment on the flexible carbon-based film; the activator solution pool is used to fully contact the flexible carbon-based film with the activator solution; the drop coating component is used to drop the activator solution onto the surface of the flexible carbon-based film material; the first drying component is used to dry the activator solution on the carbon-based film material;
[0026] The laser carbonization device is used to emit a second laser beam to perform cross-overlapping scanning on the carbon-based thin film material loaded with activator crystals;
[0027] The laser graphitization device is used to emit a third laser beam to induce and activate the composite film;
[0028] The Joule heating device comprises a positive high-voltage voltage roller group and a negative high-voltage voltage roller group, each of which comprises a plurality of high-voltage voltage rollers arranged side by side, and the high-voltage voltage rollers can rotate around their own axes, and the axes of the high-voltage voltage rollers are tangent to the conveying direction of the activated graphene film material; the high-voltage voltage rollers of the positive high-voltage voltage roller group are connected to the positive electrode of the power supply, and the high-voltage voltage rollers of the negative high-voltage voltage roller group are connected to the positive electrode of the power supply, and a processing section is formed between the positive high-voltage voltage roller group and the negative high-voltage voltage roller group, and the activated graphene film material passes through the processing section, and the positive high-voltage voltage roller group and the negative high-voltage voltage roller group roll the activated graphene film material;
[0029] The post-processing device comprises a neutralization solution pool, a deionized water pool, and a second drying component which are arranged in sequence. The neutralization solution pool and the deionized water pool are both used for cleaning the activated graphene membrane material; and the second drying component is used for drying the activated graphene membrane material.
[0030] A technical solution in the present invention can have the following beneficial effects:
[0031] The present invention uses a flexible carbon-based film material as a carbon precursor material, performs a hydrophilic modification treatment on the flexible carbon-based film material through a first laser beam, uniformly coats the activator on the flexible substrate, and then uses a second laser beam to achieve a fully uniform mixing of the activator and the carbon material on the flexible carbon-based film material after drying, so that the activator fully reacts under the action of a third laser beam, and then performs a high-temperature pyrolysis treatment through Joule heating. The strong Coulomb force generated by the high-temperature pyrolysis treatment helps to overcome the van der Waals force between graphene nanostructures, thereby inhibiting agglomeration and promoting the formation of micro-nano porous structures. The porous graphene film prepared by the preparation method can have a specific surface area of 1400 to 2000 m 2 / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a nitrogen adsorption-desorption curve diagram of the porous graphene film obtained in Example 1 of the present invention;
[0033] Figure 2 is a pore size distribution diagram of the porous graphene film obtained in Example 1 of the present invention;
[0034] Figure 3 is a schematic structural diagram of a processing device for a porous graphene film in one embodiment of the present invention;
[0035] In the accompanying drawings: an unwinding device 1, a laser pre-treatment device 2, a first laser component 21, an activator solution pool 22, a drip coating component 23, a first drying component 24, a laser carbonization device 3, a laser graphitization device 4, a Joule heating device 5, a positive high-voltage voltage roller group 51, a negative high-voltage voltage roller group 52, a high-voltage voltage roller 501, a post-treatment device 6, a neutralization solution pool 61, a deionized water pool 62, a second drying component 63, and a winding device 7. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0037] In the description of the present invention, it is necessary to understand that the terms "longitudinal", "lateral", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, features defined as "first" or "second" may explicitly or implicitly include one or more of the features, and are used to distinguish and describe features, without distinction of order or importance.
[0038] In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0039] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0040] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0042] Please refer to Figures 1 to 3 The present invention provides a method for preparing a porous graphene film, comprising the following steps:
[0043] S1: Select a flexible carbon-based film material, perform a hydrophilic modification treatment on the surface of the flexible carbon-based film material by a first laser beam, then uniformly coat an activator solution on the surface of the flexible carbon-based film material, and allow the activator solution to crystallize on the surface of the flexible carbon-based film material to obtain a carbon-based film material loaded with activator crystals;
[0044] S2: Cross-overlap scanning of the carbon-based film material loaded with activator crystals by a second laser beam to obtain a composite film, wherein the upper layer of the composite film is a uniform mixture of the carbon material and the activator, and the lower layer of the composite film is a flexible carbon-based film material;
[0045] S3: Inducing and activating the composite film with a third laser beam to obtain an activated graphene film material;
[0046] S4: using a high voltage roller to perform high temperature pyrolysis treatment on the activated graphene film material;
[0047] S5: Cleaning and drying the activated graphene membrane material in step S4 to obtain a porous graphene film.
[0048] In the preparation method of the porous graphene film, the surface of the flexible carbon-based film material is firstly treated with hydrophilicity by a first laser beam, so that the activator solution can be evenly coated on the flexible carbon-based film material, and then the activator solution is dried to make the activator crystallize on the surface of the flexible carbon-based film material; then, a second laser beam is used to perform rapid cross-overlapping scanning. Since the surface of the flexible carbon-based film material is treated with hydrophilicity, the activator crystals on the surface of the flexible carbon-based film material are distributed more concentratedly. A part of the activator crystals react with the carbon material on the flexible carbon-based film material under the laser energy provided by the second laser beam, thereby realizing carbonization of the carbon-based film material and forming a carbonized material; while another part of the activator crystals fail to participate in the reaction due to a short action time. Under the rapid scanning of the second laser beam, this part of the remaining activator crystals enters the interior of the carbonized material, and the carbonized material is formed by most of the activator crystals. The method comprises the following steps: the first step is to prepare a composite film of a carbonized material and a certain amount of graphene material, and the remaining activator crystals are fully mixed with the remaining carbon material, so as to obtain a composite film in which the upper layer is a uniform mixture of carbon material and activator and the lower layer is a flexible carbon-based film material; then, a third laser beam is used for induction and activation. Due to the highly concentrated energy of the third laser beam, it is easy to generate high pressure and high temperature at the irradiation point. Under the instantaneous high temperature and high pressure provided by the third laser beam, the activator entering the carbonized material and the carbon material that fails to participate in the reaction undergo further activation reaction, and more levels of pores are formed inside the carbonized material, so as to obtain an activated porous graphene film with a higher specific surface area; finally, a high-temperature pyrolysis treatment is carried out using the Joule heat generated by a high-voltage roller to remove amorphous carbon on the activated porous graphene film, so as to form a porous graphene film with a high specific surface area while improving the degree of graphitization.
[0049] The present invention uses a flexible carbon-based film material as a carbon precursor material, performs a hydrophilic modification treatment on the flexible carbon-based film material through a first laser beam, uniformly coats the activator on the flexible substrate, and then uses a second laser beam to achieve a fully uniform mixing of the activator and the carbon material on the flexible carbon-based film material after drying, so that the activator fully reacts under the action of a third laser beam, and then performs a high-temperature pyrolysis treatment through Joule heating. The strong Coulomb force generated by the high-temperature pyrolysis treatment helps to overcome the van der Waals force between graphene nanostructures, thereby inhibiting agglomeration and promoting the formation of micro-nano porous structures. The porous graphene film prepared by the preparation method can have a specific surface area of 1400 to 2000 m 2 / g.
[0050] The method for preparing the porous graphene film can achieve the activation of nanopores on the surface of graphene with a multi-level pore structure by changing the laser parameters of the second laser beam and the third laser beam, the type of activator, the voltage of the high-voltage voltage roller, the temperature of the high-temperature pyrolysis treatment and the duration of the high-temperature pyrolysis treatment with simple steps and flexible operability, thereby controlling the size of the pore structure to control the specific surface area of the graphene film and prepare a graphene film with an ultra-high specific surface area.
[0051] The formation process of porous graphene mainly includes three parts:
[0052] 1. Use the cross-overlapping scanning of the second laser beam to fully mix the activator and the carbon material, and carbonize the carbon material, so that part of the unreacted activator enters the interior of the carbonized material, so that the activator can participate in the reaction in deeper holes;
[0053] 2. Using a third laser beam to in-situ laser induce and activate the uniform mixture of the upper carbon material and the activator, under the action of the third laser beam, the remaining activator and the carbon material undergo further activation reaction, and multi-level holes grow from the inside of the graphene, promoting the formation of a microporous structure, thereby increasing the specific surface area of the graphene film;
[0054] 3. Using high-temperature pyrolysis treatment, the activated graphene film material is pyrolyzed at high temperature and high pressure to remove amorphous carbon in the graphene film. The decomposition of amorphous carbon leaves many vacancies on the graphene material, forming many nanopores. When the activator contains transition metal ions, the transition metal ions are embedded in the carbon lattice of the porous graphene during the activation process, resulting in an increase in the carbon lattice spacing.
[0055] Finally, the porous graphene film prepared through the above steps can be washed and dried to obtain a porous graphene film with a high specific surface area, and finally the porous graphene film is collected by a winding device.
[0056] The activator can be one or more of potassium hydroxide, zinc chloride, sodium hydroxide, potassium carbonate, copper chloride and phosphoric acid. The above activators have good activation effects on graphene and are conducive to the preparation of porous graphene structures.
[0057] In step S4, the high-voltage voltage-carrying roller includes a plurality of positively charged high-voltage voltage-carrying rollers and a plurality of negatively charged high-voltage voltage-carrying rollers. The plurality of positively charged high-voltage voltage-carrying rollers are combined into a positive high-voltage voltage-carrying roller group, and the plurality of negatively charged high-voltage voltage-carrying rollers are combined into a negative high-voltage voltage-carrying roller group. A processing gap is formed between the positive high-voltage voltage-carrying roller group and the negative high-voltage voltage-carrying roller group. The activated graphene film passes through the processing gap and forms a conductive circuit with the high-voltage voltage-carrying roller group to achieve Joule heating, and is rolled by the upper and lower high-voltage voltage-carrying rollers.
[0058] Specifically, in step S1, the hydrophilic modification step includes: scanning a first laser beam on the smooth surface of the carbon-based thin film material, and processing a microstructure array pattern with a spacing of 40 to 100 μm and a depth of 10 to 15 μm, wherein the area of the microstructure array pattern is a surface modification area, and the area without the processed microstructure array pattern is a non-surface modification area.
[0059] The microstructure array pattern can be a pattern array of a straight line, a square, an equilateral triangle or an equilateral hexagon. After the surface modification, the area of the microstructure array pattern is hydrophilic, which is convenient for the attachment of the activator solution, so that the activator solution can form crystals at the designated position, forming a crystal pattern corresponding to the microstructure array pattern. Due to the difference in the distribution of the activator solution, the specific surface areas of the surface modified area and the non-surface modified area on the flexible carbon-based film material are different, and the specific surface area of the porous graphene structure on the surface modified area is higher than the specific surface area of the porous graphene structure on the non-surface modified area. The distribution and size of the microstructure array pattern can be controlled to control the distribution and shape of the high specific surface area porous graphene structure on the flexible carbon-based film material. The straight line is specifically a pattern array formed by a combination of multiple straight lines.
[0060] The laser scanning speed of the first laser beam is 750-850 mm / s, and the laser power of the first laser beam is 13.5-14.5 W.
[0061] Specifically, in step S1, the coating step of the activator solution includes: first immersing the flexible carbon-based film material after hydrophilic modification into the activator solution to form a liquid film on the surface modified area; then taking out the flexible carbon-based film material after hydrophilic modification, and continuing to add the activator solution to the surface modified area, so that the activator solution evenly and completely covers the surface modified area; the thickness of the activator solution after crystallization is ≤15μm.
[0062] First, immerse the surface-modified flexible carbon-based film material in an activator solution, which has a certain surface tension. Using the boundary formed by the difference in hydrophilicity and hydrophobicity between the surface-modified area and the non-surface-modified area, a thin layer of activator solution liquid film is formed on the surface-modified area; after taking out the flexible carbon-based film material, the activator solution is replenished using a drop coating device. The above coating method is conducive to the uniform adhesion of the activator solution to the surface-modified area, and two areas with different specific surface areas, the surface-modified area and the non-surface-modified area, are formed on the flexible carbon-based film material, thereby controlling the distribution of the porous graphene structure and making the processed porous graphene film have better flexibility and foldability.
[0063] The pattern depth of the microstructure array is 10-15 μm, so the thickness of the activator solution after crystallization should be ≤15 μm.
[0064] Specifically, in step S1, the flexible carbon-based film material includes one of polyimide film, polyimide paper, lignin biomass film, chitosan biomass film, phenolic resin and polybenzoxazine resin; the thickness of the flexible carbon-based film material is 50 to 200 μm.
[0065] In a specific embodiment of the present invention, the flexible carbon-based film material can be selected from films made of carbon-containing materials such as polyimide film, polyimide paper, lignin biomass film, chitosan biomass film, phenolic resin and polybenzoxazine resin to provide a carbon source. The thickness of the flexible carbon-based film material is 50 to 200 μm. If the film thickness is too small, it is not enough to generate high-quality graphene; if the film thickness is too large, too much carbon source will increase the difficulty of processing, and when the conductivity of the carbon source is low, it will affect the effect of discharge machining.
[0066] Specifically, in the step S1, the activator solution is crystallized on the surface of the flexible carbon-based film material by heating and drying, the drying temperature is 60 to 100° C., and the drying time is 5 to 15 minutes.
[0067] The activator solution is dried by a drying device, and the activator solution can fully participate in the reaction only after it crystallizes. Although the activator can achieve a certain activation effect in the solution state, due to the physical properties of the liquid itself, the activator solution will flow randomly and non-directionally during the processing, which is difficult to control.
[0068] Specifically, in step S2, the second laser beam is emitted by an ultraviolet laser or a mid-infrared carbon dioxide laser;
[0069] The second laser beam performs cross-overlap scanning in a parallel scanning mode, the laser scanning direction is perpendicular to the transmission direction of the carbon-based thin film material loaded with activator crystals, the number of cross-overlap scanning is 5 to 10 times, and the scanning speed is 200 to 300 mm / s;
[0070] When using a UV picosecond laser for cross-overlap scanning, the laser power is 8.5 to 9.5 W and the laser scanning interval is 12.7 to 17.5 μm;
[0071] The ratio of the thickness of the uniform mixture of the upper carbon material and the activator of the composite film to the thickness of the lower flexible substrate is not less than 1:2.
[0072] When a mid-infrared carbon dioxide continuous laser is used for cross-overlap scanning, the laser power is 8 to 10 W and the laser scanning interval is 20 to 30 μm.
[0073] The second laser beam adopts parallel cross-overlapping scanning and a gradually progressive scanning method; the energy of the second laser beam should be absorbed by the carbon-based film material. Under the instantaneous local high temperature generated by the second laser beam irradiation, the activator and the carbon-based film material undergo a chemical reaction, and the carbon atoms in the reaction area are released in the form of gas, leaving many nanopores; the other part of the activator that does not participate in the reaction enters the interior of the carbon material during multiple overlapping scanning processes. For the purpose of industrial production, to improve processing efficiency, a laser scanning speed of 200 to 300 mm / s is selected under the condition of ensuring carbonization. In a specific embodiment of the present invention, the gradually progressive scanning method refers to the laser beam gradually scanning from left to right and downward line by line.
[0074] In order to ensure that the activator can be evenly mixed with the carbide, a smaller laser scanning spacing should be used to achieve uniform doping of the activator. Since the lasers generated by different lasers are different, the laser scanning spacing of the second laser beam emitted by different lasers is also adjusted. When using ultraviolet picosecond lasers for cross-overlap scanning, the laser scanning spacing is 12.7-17.5μm, and when using mid-infrared carbon dioxide continuous lasers for cross-overlap scanning, the laser scanning spacing is 20-30μm.
[0075] In step S2, the processing is directly carried out under air at normal temperature and pressure. However, the humidity in some areas is high. In order to prevent the activator crystals from deliquescing in the air environment, the temperature of the processing environment of step S2 can be adjusted to maintain the processing environment of step S2 at 55-75°C to ensure the dryness of the processing environment.
[0076] In a preferred embodiment of the present invention, the ratio of the thickness of the uniform mixture of the upper carbon material and the activator of the composite film to the thickness of the lower flexible substrate is not less than 1:2; if the ratio of the thickness of the upper mixture is too low, the graphene film is likely to fall off during subsequent laser scanning, limiting the adjustable parameter range of the laser, thereby limiting the thickness of the graphene film.
[0077] Specifically, in step S3, the third laser beam is emitted by an ultraviolet picosecond laser, the scanning mode is a parallel scanning mode, the laser scanning direction is perpendicular to the transmission direction of the composite film, the laser power is 6.5-7.5W, and the scanning speed is 40-80mm / s; and the composite film is placed in an inert gas atmosphere for the third laser beam scanning; the wavelength of the ultraviolet picosecond laser is ≤355nm, and the laser pulse width is ≤12ps.
[0078] In step S3, the UV picosecond laser scanning mode is parallel scanning and gradually progressive; the UV picosecond laser power is 6.5-7.5 W. Since the activator and graphene need a certain reaction time, and the laser speed is too fast to limit the film processing thickness, the laser is difficult to play a role, so the scanning speed should be selected to be 40-80 mm / s to achieve a good processing effect.
[0079] The wavelength of the ultraviolet picosecond laser is ≤355nm, and the laser pulse width is ≤12ps. The shorter the laser wavelength, the more photon energy it can provide, promoting the activation reaction of graphene and generating a more complex pore structure. In addition, the narrower the laser pulse width, the higher the instantaneous energy density it provides, which is conducive to the preparation of graphene films with micro-nano porous structures.
[0080] In step S3, the processing needs to be carried out in an inert gas atmosphere so that there is no oxygen involved in the entire reaction process of step S3, so as to avoid the introduction of more oxygen-containing groups, and the original oxygen-containing groups are released in the form of gas, thereby improving the conductivity of graphene. It should be noted that when there are no water molecules in the processing environment, no measures are needed to prevent the deliquescence of the activator crystals.
[0081] Specifically, in step S4, the voltage of the high-voltage voltage roller is 50-150V, the logarithm is 2-6, the temperature of the high-temperature pyrolysis treatment is 200-600°C, and the duration of the high-temperature pyrolysis treatment is 15-30 minutes.
[0082] Through the above steps, Joule heating of the porous graphene film is achieved by rolling with a high-voltage voltage roller. The temperature of the Joule heating can be adjusted by changing the voltage and logarithm to promote further activation reaction of the activator. The high-temperature pyrolysis is achieved by the powerful heat generated by the Joule heat to remove amorphous carbon and improve the degree of graphitization of the graphene film.
[0083] In specific practice, the length of the processing gap between the positive high-voltage voltage roller group 51 and the negative high-voltage voltage roller group 52, as well as the unwinding speed of the unwinding device 1 and the winding speed of the winding device 7 jointly determine the duration of Joule heating, that is, the insulation time. Since the graphene film also has good thermal conductivity, the heating time can be ignored.
[0084] The voltage of the high-voltage roller is 50-150V. If the discharge voltage is too low, it will lead to insufficient energy and insufficient temperature to meet the reaction requirements, resulting in a decrease in film performance; if the discharge voltage is too high, the strong Coulomb force will destroy the surface structure of graphene, causing the graphene to fall off.
[0085] Specifically, in step S5, the cleaning and drying steps include: soaking the activated graphene membrane material treated with high-temperature pyrolysis in a neutralization solution and hot deionized water in sequence, wherein the temperature of the hot deionized water is 60-70° C., and the soaking time in the neutralization solution and the soaking time in the deionized water are both 5-20 minutes; then washing in room temperature deionized water until the pH value of the washed deionized water is neutral, and drying.
[0086] The role of the neutralization solution is to remove excess activator, while deionized water can enter the nanopores and has a better cleaning effect. The neutralization solution used corresponds to the activator material. If the activator material is an acidic activator, the cleaning solution should be an alkaline dilute solution. If the activator material is an alkaline activator, the cleaning solution should be an acidic dilute solution. The above-mentioned cleaning and drying treatment can remove impurities from the porous graphene film and improve the performance of the porous graphene film.
[0087] The present invention also provides a processing device for a porous graphene film, which is used to implement the above-mentioned method for preparing the porous graphene film, comprising an unwinding device 1, a laser pre-processing device 2, a laser carbonization device 3, a laser graphitization device 4, a Joule heating device 5, a post-processing device 6 and a winding device 7 which are arranged in sequence; the unwinding device 1 is used to unwind the flexible carbon-based film, and the winding device 7 is used to wind the porous graphene film;
[0088] The laser pre-treatment device 2 includes a first laser component 21, an activator solution pool 22, a drop coating component 23 and a first drying component 24 which are arranged in sequence; the first laser component 21 is used to emit a first laser beam and perform surface hydrophilic treatment; the activator solution pool 22 is used to fully contact the flexible carbon-based film with the activator solution; the drop coating component 23 is used to drop the activator solution onto the surface of the flexible carbon-based film material; the first drying component 24 is used to dry the activator solution on the carbon-based film material;
[0089] The laser carbonization device 3 is used to emit a second laser beam to perform cross-overlapping scanning on the carbon-based thin film material loaded with activator crystals;
[0090] The laser graphitization device 4 is used to emit a third laser beam to induce and activate the composite film;
[0091] The Joule heating device 5 includes a positive high-voltage voltage roller group 51 and a negative high-voltage voltage roller group 52, each of which includes a plurality of high-voltage voltage rollers 501 arranged side by side, and the high-voltage voltage rollers 501 can rotate around their own axes, and the axes of the high-voltage voltage rollers are tangent to the conveying direction of the activated graphene film material; the high-voltage voltage rollers 501 of the positive high-voltage voltage roller group 51 are connected to the positive pole of the power supply, and the high-voltage voltage rollers 501 of the negative high-voltage voltage roller group 52 are connected to the positive pole of the power supply, and a processing area is formed between the positive high-voltage voltage roller group 51 and the negative high-voltage voltage roller group 52, and the activated graphene film material passes through the processing area, and the positive high-voltage voltage roller group 51 and the negative high-voltage voltage roller group 52 roll the activated graphene film material;
[0092] The post-processing device 6 includes a neutralization solution pool 61, a deionized water pool 62, and a second drying component 63 which are arranged in sequence. The neutralization solution pool 61 and the deionized water pool 62 are both used to clean the activated graphene membrane material; the second drying component 63 is used to dry the activated graphene membrane material.
[0093] The device of the present invention utilizes an unwinding device and a winding device. Based on the roll-to-roll process and the large area and flexibility of the flexible carbon-based film material, an activated graphene film with a large area and a high specific surface area can be efficiently processed. Not only is the process simple, but it also has strong controllability, which can greatly reduce the manufacturing cost and is conducive to industrial large-scale production.
[0094] Example 1
[0095] A method for preparing a porous graphene film comprises the following steps:
[0096] A polyimide film with a thickness of 125 μm is selected, the polyimide film is unwound by an unwinding device, a first laser beam is scanned on a smooth surface of the polyimide film, a scanning speed of the first laser beam is 800 mm / s, a laser power of the first laser beam is 14 W, and a microstructure array pattern with a pitch of 63.5 μm and a depth of 10 μm is processed;
[0097] Subsequently, a 100 g / L potassium hydroxide solution was used as an activator solution. The polyimide film was first passed through a 100 g / L potassium hydroxide solution, and then the 100 g / L potassium hydroxide solution was dripped into the surface modified area through a drop coating device, so that the activator solution was evenly covered on the surface modified area of the polyimide film. The loading amount of the activator per unit area was twice the carbon content of the polyimide film; the drying temperature was 95°C, and the drying time was 10 minutes;
[0098] A second laser beam was emitted by an ultraviolet picosecond laser, and the polyimide film loaded with activator crystals was cross-overlapped and scanned by the second laser beam to obtain a composite film with an upper layer of a uniform mixture of carbon material and activator and a lower layer of a flexible substrate, wherein the thickness of the uniform mixture of carbon material and activator and the thickness of the lower flexible substrate were in a ratio of 1:2; the laser scanning speed of the second laser beam was 200 mm / s, the laser power of the second laser beam was 8.75 W, the laser scanning interval of the second laser beam was 12.7 μm, the defocus distance of the second laser beam was -5 mm, and the laser scanning mode was parallel overlapping scanning from left to right, and the laser processing environment temperature was controlled to be 75° C. during the processing;
[0099] A UV picosecond laser is used to emit a third laser beam, and the composite film is laser induced and activated by the third second laser beam. The laser scanning speed of the third laser beam is 60 mm / s, the laser power of the third laser beam is 6.65 W, the laser scanning interval of the third laser beam is 27 μm, and the defocus distance of the third laser beam is -9 mm. The wavelength of the UV picosecond laser is 355 nm, the laser pulse width is 12 ps, and the laser scanning mode is parallel overlapping scanning from left to right, and the laser scanning mode is gradually progressive. Argon gas is introduced during the processing, and the argon gas flow rate is 100 cm 3 / min, to obtain activated graphene membrane material;
[0100] The roll-to-roll Joule heating process is realized by high-voltage voltage rollers. A DC voltage is applied between the positive high-voltage voltage roller group and the negative high-voltage voltage roller group. The voltage parameter is 138V and the logarithm is 3. The Joule heating temperature reaches 600°C and the insulation time is 30 minutes. The activated graphene film material passes through the positive high-voltage voltage roller group and the negative high-voltage voltage roller group to form a processing gap.
[0101] The activated graphene membrane treated by high-temperature pyrolysis was first immersed in a 0.1M dilute hydrochloric acid solution for 5 minutes, then immersed in 60°C hot deionized water for 20 minutes, and then washed with room temperature deionized water until the pH value of the washed deionized water was neutral, and finally dried to obtain a porous graphene film.
[0102] Comparative Example 1
[0103] A method for preparing a porous graphene film comprises the following steps:
[0104] A polyimide film with a thickness of 125 μm is selected, the polyimide film is unwound by an unwinding device, a first laser beam is scanned on a smooth surface of the polyimide film, a scanning speed of the first laser beam is 800 mm / s, a laser power of the first laser beam is 14 W, and a microstructure array pattern with a pitch of 63.5 μm and a depth of 10 μm is processed;
[0105] Subsequently, a 100 g / L potassium hydroxide solution was used as an activator solution. The polyimide film was first passed through a 100 g / L potassium hydroxide solution, and then the 100 g / L potassium hydroxide solution was dripped into the surface modified area through a drop coating device, so that the activator solution was evenly covered on the surface modified area of the polyimide film. The loading amount of the activator per unit area was twice the carbon content of the polyimide film; the drying temperature was 95°C, and the drying time was 10 minutes;
[0106] A second laser beam was emitted by an ultraviolet picosecond laser, and the polyimide film loaded with activator crystals was cross-overlapped and scanned by the second laser beam to obtain a composite film with an upper layer of a uniform mixture of carbon material and activator and a lower layer of a flexible substrate, wherein the thickness of the uniform mixture of carbon material and activator and the thickness of the lower flexible substrate were in a ratio of 1:2; the laser scanning speed of the second laser beam was 200 mm / s, the laser power of the second laser beam was 8.75 W, the laser scanning interval of the second laser beam was 12.7 μm, the defocus distance of the second laser beam was -5 mm, and the laser scanning mode was parallel overlapping scanning from left to right, and the laser processing environment temperature was controlled to be 75° C. during the processing;
[0107] A UV picosecond laser is used to emit a third laser beam, and the composite film is laser induced and activated by the third laser beam. The laser scanning speed of the third laser beam is 200 mm / s, the laser power of the third laser beam is 8.75 W, the laser scanning interval of the third laser beam is 12.7 μm, the defocus distance of the third laser beam is -5 mm, the wavelength of the UV picosecond laser is 355 nm, the laser pulse width is 12 ps, and the laser scanning mode is parallel overlapping scanning from left to right, and the method is gradually progressive; argon gas is introduced during the processing, and the argon gas flow rate is 100 cm 3 / min, to obtain activated graphene membrane material;
[0108] The roll-to-roll Joule heating process is realized by high-voltage voltage rollers. A DC voltage is applied between the positive high-voltage voltage roller group and the negative high-voltage voltage roller group. The voltage parameter is 138V and the logarithm is 3. The Joule heating temperature reaches 600°C and the insulation time is 30 minutes. The activated graphene film material passes through the positive high-voltage voltage roller group and the negative high-voltage voltage roller group to form a processing gap.
[0109] The activated graphene membrane treated by high-temperature pyrolysis was first immersed in a 0.1M dilute hydrochloric acid solution for 5 minutes, then immersed in 60°C hot deionized water for 20 minutes, and then washed with room temperature deionized water until the pH value of the washed deionized water was neutral, and finally dried to obtain a porous graphene film.
[0110] Comparative Example 2
[0111] The steps of Comparative Example 2 are the same as those of Example 1, except that an infrared carbon dioxide laser is used to emit the second laser beam, the laser scanning speed of the second laser beam is 200 mm / s, the laser power of the second laser beam is 8 W, the laser scanning spacing of the second laser beam is 27 μm, and the defocus distance of the second laser beam is -1 mm.
[0112] Comparative Example 3
[0113] A method for preparing a porous graphene film comprises the following steps:
[0114] A polyimide film with a thickness of 125 μm is selected, the polyimide film is unwound by an unwinding device, a first laser beam is scanned on a smooth surface of the polyimide film, a scanning speed of the first laser beam is 800 mm / s, a laser power of the first laser beam is 14 W, and a microstructure array pattern with a pitch of 63.5 μm and a depth of 10 μm is processed;
[0115] Subsequently, a 100 g / L potassium hydroxide solution was used as an activator solution. The polyimide film was first passed through a 100 g / L potassium hydroxide solution, and then the 100 g / L potassium hydroxide solution was dripped into the surface modified area through a drop coating device, so that the activator solution was evenly covered on the surface modified area of the polyimide film. The loading amount of the activator per unit area was twice the carbon content of the polyimide film; the drying temperature was 95°C, and the drying time was 10 minutes;
[0116] A UV picosecond laser is used to emit a second laser beam, and the second laser beam is used to perform laser induction and activation on the polyimide film loaded with activator crystals. The laser scanning speed of the second laser beam is 60 mm / s, the laser power of the second laser beam is 6.65 W, the laser scanning interval of the second laser beam is 27 μm, the defocus distance of the second laser beam is -9 mm, and the laser scanning mode is parallel overlapping scanning from left to right, and the laser processing environment temperature is controlled to be 75°C during the processing;
[0117] The roll-to-roll Joule heating process is realized by high-voltage voltage rollers. A DC voltage is applied between the positive high-voltage voltage roller group and the negative high-voltage voltage roller group. The voltage parameter is 138V and the logarithm is 3. The Joule heating temperature reaches 600°C and the insulation time is 30 minutes. The activated graphene film material passes through the positive high-voltage voltage roller group and the negative high-voltage voltage roller group to form a processing gap.
[0118] The activated graphene membrane treated by high-temperature pyrolysis was first immersed in a 0.1M dilute hydrochloric acid solution for 5 minutes, then immersed in 60°C hot deionized water for 20 minutes, and then washed with room temperature deionized water until the pH value of the washed deionized water was neutral, and finally dried to obtain a porous graphene film.
[0119] The porous graphene films obtained in Example 1 and Comparative Examples 1 to 3 were subjected to a BET specific surface area test and a sheet resistance measurement of the activated graphene films was performed using a four-probe tester. The measurement results are shown in Table 1.
[0120] Table 1 - Test results
[0121]
[0122] From the test results in the above table, it can be seen that, compared with Example 1 and Comparative Example 1, the excessively high scanning speed of the third laser beam is not conducive to the processing of the porous graphene film, the activation reaction between the activator and the graphene requires a certain amount of action time, and a laser speed that is too fast will limit the processing thickness, and the laser energy is difficult to play a role; in addition, in the third laser beam, medium laser power is conducive to the activation of graphene and the formation of micropores, and the local high temperature provided by the higher laser power will destroy the structure of the graphene.
[0123] Comparative Example 1 and Comparative Example 2 show that the shorter the laser wavelength, the more photon energy it provides, which can promote the activation reaction inside the graphene, thereby generating more developed holes. The ultra-high instantaneous energy density that the laser can provide is conducive to the processing of micro-nano porous graphene films.
[0124] Comparative Example 1 and Comparative Example 3 show that the porous graphene film processed by the present technical solution has a higher specific surface area and a richer pore structure than the graphene film processed by one-step laser. Since Comparative Example 3 directly performs laser induction and activation, the activator and the carbon material are not fully mixed, and the activation of the deep pore structure of the graphene film cannot be achieved.
[0125] The porous graphene film obtained in Example 1 was subjected to nitrogen adsorption and desorption test and pore size distribution test. The results are shown in Figure 1 and Figure 2 .
[0126] according to Figure 1 and Figure 2 It can be obtained that the high specific surface area graphene film processed in Example 1 has a high specific surface area and a pore size mainly distributed in the range of 0 to 2 nm, which belongs to micropores; due to the cross-overlapping scanning of the second laser beam, the activator and the carbon material are evenly mixed, which is conducive to the generation of micropore-scale holes; in addition, the transition metal ions in the activator are embedded in the graphene after the reaction, which is conducive to the generation of micropores; Joule heating causes high-temperature pyrolysis, breaks the graphene structure, eliminates the original amorphous carbon while promoting the activation reaction, improves the degree of graphitization, and increases the number of nanoscale holes, so as to obtain a specific surface area of up to 1000 to 1500 m 2 / g activated graphene film.
[0127] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific embodiments of the present invention without creative work, and these equivalent variations or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing a porous graphene film, characterized in that: The following steps are involved: S1: Select a flexible carbon-based film material, perform a hydrophilic modification treatment on the surface of the flexible carbon-based film material by a first laser beam, then uniformly coat an activator solution on the surface of the flexible carbon-based film material, and allow the activator solution to crystallize on the surface of the flexible carbon-based film material to obtain a carbon-based film material loaded with activator crystals; S2: Cross-overlap scanning of the carbon-based film material loaded with activator crystals by a second laser beam to obtain a composite film, wherein the upper layer of the composite film is a uniform mixture of the carbon material and the activator, and the lower layer of the composite film is a flexible carbon-based film material; S3: Inducing and activating the composite film with a third laser beam to obtain an activated graphene film material; S4: using a high voltage roller to perform high temperature pyrolysis treatment on the activated graphene film material; S5: cleaning and drying the activated graphene membrane material in step S4 to obtain a porous graphene membrane; In the step S1, the hydrophilic modification step includes: scanning a first laser beam on the smooth surface of the carbon-based thin film material, and processing a microstructure array pattern with a pitch of 40 to 100 μm and a depth of 10 to 15 μm, wherein the area of the microstructure array pattern is a surface modification area, and the area without the microstructure array pattern is a non-surface modification area; The coating step of the activator solution comprises: firstly immersing the flexible carbon-based film material after the hydrophilic modification into the activator solution to form a liquid film on the surface modification area; then taking out the flexible carbon-based film material after the hydrophilic modification, and continuously adding the activator solution to the surface modification area, so that the activator solution uniformly and completely covers the surface modification area; the thickness of the activator solution after crystallization is ≤15 μm; In the step S2, the second laser beam is emitted by an ultraviolet laser or a mid-infrared carbon dioxide laser; The second laser beam performs cross-overlap scanning in a parallel scanning mode, the laser scanning direction is perpendicular to the transmission direction of the carbon-based thin film material loaded with activator crystals, the number of cross-overlap scanning is 5 to 10 times, and the scanning speed is 200 to 300 mm / s; When using a UV picosecond laser for cross-overlap scanning, the laser power is 8.5 to 9.5 W and the laser scanning interval is 12.7 to 17.5 μm; The ratio of the thickness of the uniform mixture of the upper carbon material and the activator of the composite film to the thickness of the lower flexible substrate is not less than 1:2; When using a mid-infrared carbon dioxide continuous laser for cross-overlap scanning, the laser power is 8 to 10 W and the laser scanning interval is 20 to 30 μm; In the step S3, the third laser beam is emitted by an ultraviolet picosecond laser, the scanning mode is a parallel scanning mode, the laser scanning direction is perpendicular to the transmission direction of the composite film, the laser power is 6.5-7.5W, and the scanning speed is 40-80mm / s; and the composite film is placed in an inert gas atmosphere for the third laser beam scanning; the wavelength of the ultraviolet picosecond laser is ≤355nm, and the laser pulse width is ≤12ps.
2. The method for preparing a porous graphene film according to claim 1, characterized in that: In the step S1, the flexible carbon-based film material includes one of a polyimide film, a lignin biomass film, a chitosan biomass film, a phenolic resin and a polybenzoxazine resin; and the thickness of the flexible carbon-based film material is 50 to 200 μm.
3. The method for preparing a porous graphene film according to claim 1, characterized in that: In the step S1, the activator solution is crystallized on the surface of the flexible carbon-based film material by heating and drying, the drying temperature is 60-100° C., and the drying time is 5-15 minutes.
4. The method for preparing a porous graphene film according to claim 1, characterized in that: In step S4, the voltage of the high-voltage voltage roller is 50-150V, the logarithm is 2-6, the temperature of the high-temperature pyrolysis treatment is 200-600°C, and the duration of the high-temperature pyrolysis treatment is 15-30 minutes.
5. The method for preparing a porous graphene film according to claim 1, characterized in that: In step S5, the cleaning and drying steps include: soaking the activated graphene membrane material treated with high-temperature pyrolysis in a neutralization solution and hot deionized water in sequence, wherein the temperature of the hot deionized water is 60-70° C., and the soaking time in the neutralization solution and the soaking time in the deionized water are both 5-20 minutes; then washing in deionized water at room temperature until the pH value of the washed deionized water is neutral, and then drying.
6. A method for preparing a porous graphene film, characterized in that: A method for preparing a porous graphene film according to any one of claims 1 to 5 is implemented using a processing device for a porous graphene film, wherein the processing device comprises an unwinding device, a laser pre-processing device, a laser carbonization device, a laser graphitization device, a Joule heating device, a post-processing device and a winding device which are arranged in sequence; the unwinding device is used to unwind the flexible carbon-based film, and the winding device is used to wind the porous graphene film; The laser pre-treatment device comprises a first laser component, an activator solution pool, a drop coating component and a first drying component which are arranged in sequence; the first laser component is used to emit a first laser beam and perform surface hydrophilic treatment on the flexible carbon-based film; the activator solution pool is used to fully contact the flexible carbon-based film with the activator solution; the drop coating component is used to drop the activator solution onto the surface of the flexible carbon-based film material; the first drying component is used to dry the activator solution on the carbon-based film material; The laser carbonization device is used to emit a second laser beam to perform cross-overlapping scanning on the carbon-based thin film material loaded with activator crystals; The laser graphitization device is used to emit a third laser beam to induce and activate the composite film; The Joule heating device comprises a positive high-voltage voltage roller group and a negative high-voltage voltage roller group, each of which comprises a plurality of high-voltage voltage rollers arranged side by side, and the high-voltage voltage rollers can rotate around their own axes, and the axes of the high-voltage voltage rollers are tangent to the conveying direction of the activated graphene film material; the high-voltage voltage rollers of the positive high-voltage voltage roller group are connected to the positive electrode of the power supply, and the high-voltage voltage rollers of the negative high-voltage voltage roller group are connected to the positive electrode of the power supply, and a processing section is formed between the positive high-voltage voltage roller group and the negative high-voltage voltage roller group, and the activated graphene film material passes through the processing section, and the positive high-voltage voltage roller group and the negative high-voltage voltage roller group roll the activated graphene film material; The post-processing device comprises a neutralization solution pool, a deionized water pool, and a second drying component which are arranged in sequence. The neutralization solution pool and the deionized water pool are both used for cleaning the activated graphene membrane material; and the second drying component is used for drying the activated graphene membrane material.
Citation Information
Patent Citations
Three-dimensional porous graphene film material, preparation method and application thereof
CN117507502A
Method for constructing laser-induced graphene through multi-receptor surface transfer
CN117644275A